2009
DOI: 10.1530/eje-08-0807
|View full text |Cite
|
Sign up to set email alerts
|

Elevated basal and post-feed glucagon-like peptide 1 (GLP-1) concentrations in the neonatal period

Abstract: Background: Glucagon-like peptide 1 (GLP-1) is an incretin hormone that stimulates glucose-induced insulin secretion, increases b-cell proliferation, neogenesis and b-cell mass. In adults, plasma concentrations of amidated GLP-1 are typically within the 5-10 pmol/l range in the fasting state and increases to w50 pmol/l after ingestion of a mixed meal. Research design and methods: We measured plasma glucose, insulin and amidated forms of GLP-1 prefeed and then at 20 and 60 min post-feed following ingestion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
(39 reference statements)
1
16
0
1
Order By: Relevance
“…This finding indicates that the EIA in newborn foals is functional and highly responsive to nutrients contained in mare's milk, other than those administered in our study. Human newborn infants showed a similar GLP‐1 response after feeding milk . Mare's milk 1‐4 weeks postpartum is composed of approximately 2% fat, 3% protein, and 6% lactose .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding indicates that the EIA in newborn foals is functional and highly responsive to nutrients contained in mare's milk, other than those administered in our study. Human newborn infants showed a similar GLP‐1 response after feeding milk . Mare's milk 1‐4 weeks postpartum is composed of approximately 2% fat, 3% protein, and 6% lactose .…”
Section: Discussionmentioning
confidence: 91%
“…It could also be that newborn foals have decreased DPP‐4 activity compared to horses. Similar to foals and horses, it has been shown that human infants have higher resting GLP‐1 concentrations than adults . The dynamics of incretin secretion over time in healthy foals remain to be investigated but preliminary work from our laboratory indicates that 3‐day‐old foals have lower GLP‐1 concentrations than at birth (L.M.R./R.E.T., personal communication).…”
Section: Discussionmentioning
confidence: 94%
“…Our study design does not allow to infer when exactly those GLP-1 levels surge, but cross-sectional evidence from newborns aged 4-10 days suggests that this surge (to supra-adult concentrations) occurs within the first few days after birth. 11 The observation that pre-feeding GLP-1 levels are higher in SGA infants receiving FOF than in those receiving BRF during early infancy suggests that neonatal nutrition is a modulator of circulating GLP-1 in SGA infants and is thus a potential modulator of hypothalamic setpoints that relate to appetite and energy expenditure in subsequent life. [6][7][8][9] For example, higher concentrations of circulating GLP-1 during early infancy may be accompanied by lower hypothalamic sensitivity to GLP-1 in later life.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported similar findings. 10,11 Kawamata et al 8 speculated that these differences between infants and adults in GIP or GLP-1 levels result from a difference in the amount of enteral feeding. In preterm infants, enteral feeding is usually every 3 h, which may stimulate GIP and GLP-1 secretion to a greater level in neonates than in older children and adults.…”
Section: Discussionmentioning
confidence: 99%